Akhbar Khuttah Mishriyyah-Urduniyyah li al-Saitharah alâ Taáddud Jihât al-Qarâr fi Hamas (Tahlil al-Khitab al-Naqdy Teun A. Van Dijk - Mahliatussikah, Hanik; Aziz, Mahbub Humaidi (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This research is about critical discourse analysis using Teun A. Van Dijk's theory specialized in the discussion of the text section. Analyzing the discourse on Egyptian-Jordanian plans to control the large number of Hamas decision-makers, Van Dijk sees that the text consists of several structures/levels, which support each other. He divided it into three levels. First, the overall structure, second, the superstructure, and third, the microstructure. This type of research is qualitative research using the method of documentation and descriptive analysis of the content of the news text. In the documentation process, the researcher obtained the data from the news website alarab.co.uk. This study aims to determine the results of Teun A. Van Dijk's critical discourse analysis on the news text. The object of this study is the online news media in Arabic, alarab.co.uk, while the subject of this research is the discourse of the state of the many faces of the Hamas organization that controls decision-making. This analysis was performed on macro-structure (themes), superstructure (layouts), micro-structure (semantics: background, detail, intent, assumptions), micro-structure (structure: sentence form, coherence, and pronouns), and micro-structure (style: lexicon ), the precise structure (rhetorical: graphic, metaphor, expression) in Arabic discourse.